The Mediating Effect of Financial Management Behavior on MSME Economic Performance in Bali - Dewi, Ni Made Dwi Rosiana; Mahyuni, Luh Putu (International Journal of Economics Development Research (IJEDR), 2025)
The objective of this research is to assess the influence of financial literacy on the performance of MSMEs in Bali; the influence of financial attitudes on the performance of MSMEs in Bali; and the influence of financial technology on the performance of MSMEs in Bali. Furthermore, this study evaluates the impact of financial literacy, financial attitudes, and financial technology on financial management behavior among MSMEs in Bali. It also examines the mediating role of financial management behavior in the relationship between financial literacy, financial attitudes, and financial technology with MSME performance. Specifically, the study explores whether financial management behavior serves as a mediator in the effect of financial literacy, financial attitudes, and financial technology on the performance of MSMEs in Bali. The data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The findings indicate that financial literacy, financial attitudes, and the use of financial technology significantly and positively influence both MSME performance and financial management behavior. Moreover, these three variables exert indirect effects on MSME performance through improvements in financial management behavior, which acts as a mediating variable.